Association between risk of venous thromboembolism and mortality in patients with COVID-19. (July 2021) - Chen, Shujing; Zheng, Tianqi; Wang, Sihua; Yu, Yongfu; Wang, Peng; Song, Yuanlin; Jiang, Jinjun
Graphical abstract: Highlights: Venous thromboembolism risk associated with 30-day mortality in COVID-19 patients. Venous thromboembolism (VTE) risk assessment models (RAMs) used. Higher score of Padua, IMPROVE or Caprini VTE RAMs means higher mortality risk. Increased VTE risk associated with higher sequential organ failure assessment score. VTE RAMs indicate higher accuracy to predict 30-day mortality in these patients. Abstract: Objectives: To investigate the association of risk of venous thromboembolism with 30-day mortality in COVID-19 patients. Methods: A total of 1030 COVID-19 patients were retrospectively collected, with baseline data on demographics, sequential organ failure assessment (SOFA) score, and VTE risk assessment models (RAMs), including Padua prediction score (PPS), International Medical Prevention Registry (IMPROVE), and Caprini. Results: Thirty-day mortality increased progressively from 2% in patients at low VTE risk to 63% in those at high risk defined by PPS. Similar findings were observed in IMPROVE and Caprini scores. Progressive increases in VTE risk were also associated with higher SOFA score. High risk of VTE was independently associated with mortality regardless of adjusted gender, smoking status and some comorbidities, with hazard ratios of 29.19, 37.37 and 20.60 for PPS, IMPROVE and Caprini RAM, respectively ( P < 0.001 for all comparisons). The predictive accuracy of PPS (area under curve (AUC) 0.900), IMPROVE (AUC 0.917), or Caprini (AUC 0.861) RAM for risk of hospitalized mortality was unexpectedly strong. Conclusions: We established that the presence of a high risk of VTE identifies a group of COVID-19 patients at higher risk for mortality. Furthermore, there is a high accuracy of VTE RAMs to predict mortality in these patients.